Efektivitas Media Leaflet dalam Edukasi Pembuangan Obat yang Benar - Isnenia Isnenia; Meutia Mukarromah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Proper drug disposal is often perceived as a trivial matter by the public when dealing with medications that are no longer needed. However, improper disposal can effect on the economy, public health, and the environment. Therefore, it is essential to educate the public to improve their knowledge regarding appropriate drug disposal methods. Previous studies have shown that educational media can effectively increase public awareness and understanding. The purpose of this study was to evaluate the effectiveness of educational leaflets in enhancing public knowledge about proper drug disposal. This experimental study involved an intervention using educational leaflets. A total of 100 respondents participated in the study. The intervention was conducted over three consecutive days. Pretest and posttest data were collected to assess changes in knowledge. Univariate analysis was used to describe respondent characteristics, while bivariate analysis (Wilcoxon test) was employed to compare pretest and posttest results. Pretest data indicated that the majority of respondents had only sufficient knowledge about drug disposal. Following the intervention, the number of respondents with sufficient knowledge decreased, while those categorized as having good knowledge increased. Statistically, a p-value of 0.000 demonstrated that the use of leaflets significantly improved knowledge level. Based on the results of this study, educational interventions, such as the distribution of leaflets, can effectively enhance public knowledge about proper drug disposal.